Can intellectual capital promote the competitive advantage? Service innovation and big data analytics capabilities in a moderated mediation model - Alkhatib, Ayman Wael; Valeri, Marco (European journal of innovation management, 2024)
PurposeThis study explores the connection between intellectual capital (IC) components and the competitive advantage (CA) of the hospitality sector in Jordan through the mediating role of service innovation as well as the moderating role of big data analytics capabilities.Design/methodology/approachData were collected through a self-administered questionnaire from the hospitality sector with a sample of 402 respondents. Data were analysed using SmartPLS, a bootstrapping technique was used to analyse the data. The mediating effect for service innovation and the moderating effect for big data analytics capabilities were performed.FindingsThe results showed that the proposed moderated-mediation model was accepted because the relationships between the constructs were statistically significant. The results of the data analysis supported a positive relationship between human capital, structural capital and relational capital and the CA as well as a mediating effect of service innovation. The findings confirmed that there is a moderating relationship for big data analytics capabilities between service innovation and CA. The results illustrate the importance of IC and service innovation in enhancing CA in the Jordanian hospitality sector in light of the big data analytics capabilities.Research limitations/implicationsThis cross-sectional study provides a snapshot at a given moment in time, a methodological limitation that affects the generalisation of the limitation's results, and the results are limited to one sector.Originality/valueThis research developed a theoretical model to incorporate IC components, service innovation, big data analytics capabilities and CA. This paper offers new theoretical and practical contributions that add value to the innovation and CA literature by testing the moderated-mediation model of these constructs in the hospitality sector which has been greatly affected by the coronavirus disease 2019 (COVID-19) pandemic. This study is distinguished from other studies by highlighting the role of IC and service innovation in enhancing CA as service innovation contributes to the formation of many organisational advantages in the Jordanian hospitality sector.